Regulasi Adat dan Realitas Modern: Analisis Kebijakan Ngaben Krematorium dan Dampak Pada Struktur Sosial-Budaya Bali - Astiti, Ni Putu (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2025)
This study aims to analyze the dialectic between the spiritual obligation of Pitra Yadnya and the challenges of modernity, which are manifested in the Ngaben policy in crematoriums and its impact on the socio-cultural structure of Balinese Hindu society. The phenomenon of Ngaben in crematoriums, often termed as Ngaben Efisien or Ngaben Aluh, emerged as a real response to modern realities: limited land, soaring costs, and demands for efficiency in time and energy, which collectively threaten the tradition of mutual cooperation and the authority of the Traditional Village which is tied to the implementation of magnificent rituals. This study adopts a qualitative method with a critical policy analysis approach and is based on Giddens' structuration theory, which is relevant to observing how individual actions (choosing a crematorium) shape new social structures. Data collection was carried out through in-depth interviews with key informants selected purposively and snowballing, including crematorium managers, Jero Mangku (religious leaders), Prajuru Desa Adat (traditional village officials), and families who choose mass Ngaben or crematorium. Furthermore, participant observation and document study of the Awig-Awig and the Lontar Yama Purwana Tattwa were used to explore the theological legitimacy of the new practice. The research findings indicate that although the crematorium has been theologically legitimized by the reinterpretation of the lontar, this practice generates social tensions that erode communal cohesion, but also empowers migrants, thus demanding customary policies that balance the ritual and socio-economic dimensions.